2020
DOI: 10.1108/ijoem-05-2019-0342
|View full text |Cite
|
Sign up to set email alerts
|

Stock prices and macroeconomic information in Ghana: speed of adjustment and bi-causality analysis

Abstract: PurposeThe purpose of the paper is to investigate the causal relationships and speed of adjustment of stock prices to changes in macroeconomic information (MEI) in Ghana from 1996 to 2018 using monthly data. The paper seeks to conduct the investigation at individual MEI level rather than the composite MEI.Design/methodology/approachQuantitative approach was used in this paper. Monthly data span of 1996–2018 was used. The delay and half-life technique was used to determine the speed with which the information r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Evidence suggests that the impact of macroeconomic events on index futures trading is not always equal. Queku et al [53] use Toda, Yamamoto, and Granger's no-causality method and monthly time series data from 1996 to 2018 to investigate the causal linkages between share prices and variations in macroeconomic indicators (MEI) in Ghana. They indicate bidirectional causation between MEI (GDP, interest rate, and money supply) and share prices and a linear link flowing from MEI (currency rate and overseas direct investment) to share prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the impact of macroeconomic events on index futures trading is not always equal. Queku et al [53] use Toda, Yamamoto, and Granger's no-causality method and monthly time series data from 1996 to 2018 to investigate the causal linkages between share prices and variations in macroeconomic indicators (MEI) in Ghana. They indicate bidirectional causation between MEI (GDP, interest rate, and money supply) and share prices and a linear link flowing from MEI (currency rate and overseas direct investment) to share prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies examine the relationships between macroeconomic variables and stock prices ( 18 , 33 , 55 , 7 ; Chang et al, 2020; 34 , 51 ). Other studies investigate the effect of macroeconomic news on financial stock markets ( 1 , 15 , 16 , 17 , 19 , 2 , 25 , 54 , 9 ; Corbet et al, 2020; 35 , 53 , 63 ). Besides, two recently developed real-time, real-activity indexes describe and measure the changes in macroeconomic news surprises and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…As observed by Morales and Callaghan (2012), worldwide stock markets are becoming more interdependent, and hence, crisis happening in one country spreads faster in other countries. Queku et al (2020) also observed that market adjustment to macroeconomic indicators has improved; however, the speed of recovery has been very slow.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Additionally, the stock market is critical to a country's economy, and its interconnected movements are a leading indicator of economic crises such as recessions and depressions (Queku et al, 2020). According to Moussa and Delhoumi (2021), stock markets mediate between listed firms and investors in developed and emerging markets.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia's index has Southeast Asia's second-largest domestic market capitalization. A strong stock market suggests a healthy economy, but a long-term drop in the stock market signals economic difficulties such as recession or depression (Queku et al, 2020). According to Liang et al (2020), uncertainty in the United States has a negative effect on stock prices in eight markets.…”
Section: Introductionmentioning
confidence: 99%